The role of magnesium deficiency in the pathogenesis of hypertension and the influence of magnesium supplementation on blood pressure - literature review - Dominik Machaj; Dominik Machaj; Patrycja Baciur; Katarzyna Skowrońska; Anna Chmura (Kazimierz Wielki University, 2022)
Magnesium is a macronutrient that is very important for the proper functioning of the human body. Deficiency of this element is crucial in the development of many disorders in the proper functioning of many organ systems. The optimal level of magnesium has a significant influence on the functioning of the cardiovascular system, among others. Although the factors showing the mechanism of lowering blood pressure by magnesium ions are not fully understood, the influence of the correct concentration of magnesium in the human body on cardiovascular protection is beyond doubt. Magnesium supplementation produces positive effects in the functioning of blood vessels and in maintaining blood pressure within the normal range. In our article, we focused on the role of magnesium in maintaining normal blood pressure at the molecular, cellular and tissue levels, as well as on the impact of magnesium supplementation on reducing blood pressure.